Effectiveness of Village Fund Policies on Economic and Infrastructure Development in Bonto Jai Village - Nur Reski Magfirah; Andi Hakib (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This study examines the effectiveness of Village Fund policies in promoting economic development and infrastructure improvement in Bonto Jai Village, Bissappu District, Bantaeng Regency, Indonesia, during the 2020–2024 period. Employing a mixed-methods approach, the research integrates quantitative and qualitative analyses to provide a comprehensive evaluation of policy outcomes. Quantitative data were obtained from village budget realization reports and analyzed using an effectiveness ratio comparing planned and realized expenditures. Qualitative data were collected through observations, in-depth interviews with village officials, community leaders, and beneficiaries, as well as documentation review, to capture stakeholder perceptions and implementation dynamics. The findings indicate that Village Fund utilization in Bonto Jai Village was generally effective, with effectiveness levels ranging from 90% to 98% over the study period. Infrastructure development, particularly in agricultural support facilities such as farm roads and irrigation systems, significantly improved accessibility, mobility, and productivity. In terms of economic development, Village Fund–supported programs, including the establishment of village-owned enterprises (BUMDes), microenterprise assistance, and capacity-building initiatives, contributed to local economic activity and employment creation. Furthermore, increased community participation in village deliberation forums strengthened transparency and accountability in fund management. Despite these positive outcomes, the study identifies challenges related to unequal benefit distribution, limited community involvement in BUMDes management, and infrastructure maintenance issues. Overall, the study concludes that Village Fund policies have effectively supported local development in Bonto Jai Village, while highlighting the need for improved governance capacity, inclusive participation, and sustainability-oriented planning to enhance long-term policy impact.